2020
DOI: 10.1148/radiol.2020192230
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Liver MRI for Identifying the Macrotrabecular-Massive Subtype of Hepatocellular Carcinoma

Abstract: H epatocellular carcinoma (HCC) accounts for the majority of primary liver cancers, which are the fourth leading cause of cancer-related deaths worldwide. The burden of HCC is increasing, mainly due to the rising prevalence of obesity and nonalcoholic fatty liver disease (1). Although surveillance programs have been implemented for at-risk patients (eg, patients with cirrhosis) to detect tumors at early stages and to allow for potentially curative treatment, such patients have high recurrence rates and heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 23 publications
12
66
1
Order By: Relevance
“…Our results showed that intratumor necrosis was independently associated with MTM subtype and VETC pattern, in agreement with the findings reported by Mulé et al (11). However, the relatively narrow CIs of the estimated ORs in our study should be attributed to the higher prevalence of the two subtypes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that intratumor necrosis was independently associated with MTM subtype and VETC pattern, in agreement with the findings reported by Mulé et al (11). However, the relatively narrow CIs of the estimated ORs in our study should be attributed to the higher prevalence of the two subtypes.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, there are few studies illustrating the imaging characteristics of MTM subtype or VETC pattern in HCC. Mulé et al (11) reported that substantial necrosis at contrast-enhanced MRI was an independent predictor of MTM subtype and had high…”
mentioning
confidence: 99%
“…In this study, a metabolic gene prognostic model was constructed based on regression analysis to improve prognosis and guide the meticulous design of better treatments. Regression analysis including univariate COX regression analysis, least absolute shrinkage and selection operator (Lasso) regression analysis and multivariate COX regression analysis were widely used in the study of cancer prognosis such as hepatocellular carcinoma (Mule et al, 2020), lung adenocarcinoma (Zhu et al, 2020), bladder cancer (Jiang et al, 2020), and ovarian cancer (Ding et al, 2020). However, research into OSCC should be supplemented.…”
mentioning
confidence: 99%
“…For high-dimensional data, the least absolute shrinkage and selection operator (LASSO) method is more available to screen the predictive features from the primary data set compared with conventional regression analysis [ 9 12 ]. Tuning parameter (lambda) selection in the LASSO model uses 10-fold cross-validation [ 9 , 11 ]. By shrinking down to zero coefficient weights, LASSO regression analysis has the ability to eliminate exposures that are non-related to the outcome [ 9 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tuning parameter (lambda) selection in the LASSO model uses 10-fold cross-validation [ 9 , 11 ]. By shrinking down to zero coefficient weights, LASSO regression analysis has the ability to eliminate exposures that are non-related to the outcome [ 9 , 11 ]. In the first step of our study, we identified the independent risk factors of long-term positive SARS-CoV-2 RNA detection by using LASSO logistic regression analysis and SARS-CoV-2 RNA detection duration by using LASSO Cox regression analysis.…”
Section: Methodsmentioning
confidence: 99%